Financial risk tolerance based on gender, age, and formal education: the perspective of businesspersons - Herlina, Herlina; Gunawan, Ika; Njotoprajitno, Rosemarie Sutjiati; Gunawan, Tommy (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2024)
In the marketplace competition, every business, including those belonging to micro, small, and middle firms, must face the risk. In the optimistic view of entrepreneurs, this risk may upsurge the return. This investigation tries to verify and analyze financial risk tolerance (FRT) based on three demographic factors: gender, age, and formal education. The population comes from entrepreneurs in Bandung City, who used the snowball sampling technique to obtain the samples. Through the survey between August and October 2022, this study successfully collected 101 people. This study uses a structural equation model based on a partial least square to analyze the response through hypothesis testing. The analysis results demonstrate that males are more tolerant of financial risk than females, and age negatively affects FRT. However, formal education does not relate to FRT.